The IPTA Nashville consensus conference on post-transplant lymphoproliferative disorders after solid organ transplantation in children: IV-consensus guidelines for the management of post-transplant lymphoproliferative disorders in children and adolescents - Allen, Upton; L'Huillier, Arnaud G.; Bollard, Catherine M.; Gross, Thomas G.; Hayashi, Robert J.; Höcker, Britta; Maecker-Kolhoff, Britta; Marks, Stephen D.; Mazariegos, George Vincent; Smets, Francoise; Trappe, Ralf U.; Visner, Gary; et al. (Pediatric transplantation, 2024)
The International Pediatric Transplant Association convened an expert consensus conference to assess current evidence and develop recommendations for various aspects of care relating to post-transplant lymphoproliferative disorders (PTLD) after pediatric solid organ transplantation. This report addresses the outcomes of deliberations by the PTLD Management Working Group. A strong recommendation was made for reduction in immunosuppression as the first step in management. Similarly, strong recommendations were made for the use of the anti-CD20 monoclonal antibody (rituximab) as was the case for chemotherapy in selected scenarios. In some scenarios, there is uncoupling of the strength of the recommendations from the available evidence in situations where such evidence is lacking but collective clinical experiences drive decision-making. Of note, there are no large, randomized phase III trials of any treatment for PTLD in the pediatric age group. Current gaps and future research priorities are highlighted.